2021
DOI: 10.1002/cmdc.202100434
|View full text |Cite
|
Sign up to set email alerts
|

Sophoridine Derivatives Induce Apoptosis and Autophagy to Suppress the Growth of Triple‐Negative Breast Cancer through Inhibition of mTOR Signaling

Abstract: In order to improve the antitumor potency and therapeutic margins of natural product sophoridine, its novel nitrogen mustard carbamate derivatives were designed and synthesized. In screening their in vitro activity, we found all the tested compounds were more potent against the highly aggressive triple‐negative breast cancer cell line MDA‐MB‐231. Cellular functional assays showed that representative compounds could induce G1‐phase arrest and trigger apoptosis, evidenced by the alteration of Bax, Bcl‐2, caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our previous research has shown that LTF induced autophagy in human kidney proximal tubular cells [ 26 ]. Furthermore, previous reports demonstrated that Akt/mTOR pathway is able to negatively regulate the formation of autophagy [ 27 , 28 ]. Hence, we measured the levels of LC3-II which is a phosphatidylethanolamine-conjugated form of LC3-I and acts as a key initiator for autophagy formation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research has shown that LTF induced autophagy in human kidney proximal tubular cells [ 26 ]. Furthermore, previous reports demonstrated that Akt/mTOR pathway is able to negatively regulate the formation of autophagy [ 27 , 28 ]. Hence, we measured the levels of LC3-II which is a phosphatidylethanolamine-conjugated form of LC3-I and acts as a key initiator for autophagy formation.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research, in order to improve the antitumor potency and therapeutic margins of natural product sophoridine, its novel nitrogen mustard carbamate derivatives were designed and synthesized. [8] In these molecules, a variety of differently substituted aromatic sulfonyls have been introduced into the nitrogen atom of sophoridinic scaffold to determine the effect of these structural changes on antitumor activity. Among them, a p-chloro phenylsulfonyl-containing derivative was shown to significantly suppress the tumor growth in the triple-negative breast cancer MDA-MB-231 xenograft mouse model.…”
Section: In Vitro Evaluation and Sarmentioning
confidence: 99%
“…[6][7] More recent work from our laboratory identified several nitrogen mustard carbamate sophoridine derivatives, which have been shown to significantly suppress the tumor growth in the triple-negative breast cancer MDA-MB-231 xenograft mouse model through inhibition of mTOR signaling. [8] Both genetic and epigenetic alterations contribute to development of human cancer. [9] Pharmacologic manipulation of proteins that regulate epigenetics has emerged as a promising therapeutic area of study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that SR exhibits various clinical pharmacological activities, including anti‐arrhythmic (Song et al., 2023), anti‐inflammatory (Huang et al., 2014; Liang et al., 2022; Zhao et al., 2010), antiviral (Ren et al., 2019; Tang et al., 2022; Zhang et al., 2006), immunosuppression‐alleviating (Zhuang et al., 2020), anti‐heart failure (Hu et al., 2016), and neuroprotective activities (Liu et al., 2012). Domestic and foreign researchers have examined the growth‐inhibitory effects of SR against various cancers, such as triple‐negative breast cancer (Dai et al., 2022), lung cancer (Zhao, Hui, et al., 2021; Zhao, Zhang, et al., 2021; Zhu et al., 2020), liver cancer (Zhao, Hui, et al., 2021; Zhao, Zhang, et al., 2021), pancreatic cancer (Xu et al., 2017), and gastric cancer (Peng et al., 2020). The potential mechanism through which SR exerts its antitumor effect may involve the upregulation of intracellular reactive oxygen species (ROS) content, which results in cell cycle arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%